Investigation of Phenolic Profiles, Cytotoxic Potential and Phytochemical Screening of Different Extracts of Drynaria quercifolia J. Smith (Leaves) - Jannatul Ferdous Runa; Marjan Hossain; Md. Hasanuzzaman; Md. Ramjan Ali (Tabriz University of Medical Sciences, 2013)
Purpose: The present study is aimed to evaluate phenolic profiles, cytotoxic activity and phytochemical screening of different extracts of Drynaria quercifolia leaves. Methods: The dried and powder leaves were extracted with methanol at room temperature and the concentrated methanolic extract was fractionated by the modified Kupchan partitioning method to provide pet-ether, carbon tetrachloride, chloroform and aqueous soluble fractions. Phenolic profiles were determined by using Folin-Ciocalteau reagent, which results were expressed in gallic acid equivalent (mg of GAE/g of sample). Phytochemical properties of different extractives of plant materials were tested by the method of Trease and Evans. Brine shrimp lethality bioassay was used to investigate the cytotoxic potential of D. quercifolia. Results: The phytochemical screening revealed the potent source of different phytochemical constituents on different extractives including alkaloid, glycosides, tannin, saponins, proteins and amino acids, flavonoids, triterpenes, phenols, phytosterols and carbohydrate. In the determination of phenolic profiles, different extractives showed a significant content of phenolic compounds ranging from 103.43 -132.23 mg of GAE/g of extractive. Compared to vincristine sulfate different extractives of plant materials demonstrated moderate cytotoxic potential (having LC50 of 12.45 μg/ml, 13.02 μg/ml 15.83 μg/ml, 14.95 μg/ml and 7.612 μg/ml, respectively). Conclusion: It is concluded from this study that D. quercifolia is an excellent source of phenolic content and phytoconstitutes as well as possesses moderate cytotoxic activity.